Penanaman Nilai-Nilai Islam Dalam Membentuk Akhlak Mulia Melalui Kegiatan Mendongeng di TK Terpadu Nurul Amal Buyuk Bringkang Menganti Gresik - Nur Hudah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2019)
Islamic religious values ??are all rules or rules of good behavior, which all have been regulated by Allah SWT. These rules include how to establish a relationship with God, relationships between human beings, and relationships with nature. Implanting Islamic Values ??through Storytelling is a way to instill Islamic values ??in children with a pleasant art of storytelling where in the story there are rules or rules of behavior that have been arranged by God, how to behave to Him, to others humans or friends, and to the natural surroundings. Some of the problems that researchers want to find out through this research are: a). What is the process of planting noble morals through storytelling activities at Nuradu Amal Kindergarten Buyuk Bringkang Menganti Gresik? b). What are the advantages and disadvantages of storytelling in the cultivation of noble moral values ??in the Integrated Kindergarten Nurul Amal Buyuk Bringkang Menganti Gresik? The method used in this research is interview, observation, and documentation. The results showed that storytelling activities at Nurul Amal Buyuk Kindergarten were held every 2 weeks, with 1 hour duration, without class grouping. Fairytale material can be obtained from various sources. Before carrying out activities there are always preparations made including setting goals, preparing material, understanding content, and preparing visuals. The values ??conveyed include courtesy, courtesy, and worship. Before starting the fairy tale the teacher will condition the atmosphere first, then say hello, convey today's activities, mention the title, convey the contents of the tale, evaluate with questions and answers. The weakness of this activity according to the teachers is the atmosphere is not conducive, misunderstanding the needs of children, children's hearts are unpredictable. The advantages of this activity are the children's favorite, facilitating the delivery of values, closer teacher and children's relationships.